PENGARUH SISTEM INFORMASI PEMERINTAH DAERAH TERHADAP DISPARITAS AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH - Kalay, Vindy Nerson; Abdullah, Julie Abdullah; Junus, Onong; Saprudin, Saprudin; Masjhur, Mohamad Abdul Radjak; Yakup, Anggita Permata (KINDAI, 2025)
This study aims to examine the impact of the Regional Government Information System (SIPD) on disparities in regional financial management accountability in North Sulawesi Province. The study used primary data collected from 96 respondents through online questionnaires and field observations. A quantitative descriptive approach with simple linear regression analysis was employed. The results indicate that SIPD implementation has generally been well executed across most local governments, as reflected by high average scores for the SIPD variable. However, disparities in financial management accountability among regions persist, influenced by internal factors such as human resource capacity, technological infrastructure, and institutional readiness. The findings demonstrate that effective implementation of SIPD significantly contributes to reducing disparities in regional financial management accountability. Keywords: local government information system, disparity in local financial management accountability